1992
DOI: 10.1152/ajprenal.1992.263.5.f907
|View full text |Cite
|
Sign up to set email alerts
|

Arginine augments neither albuminuria nor albumin synthesis caused by high-protein diets in nephrosis

Abstract: Dietary protein independently modulates albuminuria (U(Alb)V) and albumin synthesis (AlbSyn) in nephrotic rats. While some amino acids are without effect on renal hemodynamics, arginine (Arg) augments renal blood flow and glomerular filtration rate, increases AlbSyn in tissue culture and isolated perfused livers, and could be one specific amino acid causing both decreased glomerular permselectivity and increased AlbSyn. Nephrotic rats were fed 10% casein (LP); 30% casein (HP); 30% casein with the inhibitor of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This effect is likely mediated by the differences in acid load associated with the two sources of protein sources, although differences in amino acid composition may contribute. We had observed that the effect of increasing dietary amino acid content on urinary protein excretion in nephrotic rats was dependent upon amino acid composition and not total amino acid load [19,20], although the acid content of these diets was not controlled.…”
Section: Effect Of Dietary Protein Restriction On Proteinuriamentioning
confidence: 99%
“…This effect is likely mediated by the differences in acid load associated with the two sources of protein sources, although differences in amino acid composition may contribute. We had observed that the effect of increasing dietary amino acid content on urinary protein excretion in nephrotic rats was dependent upon amino acid composition and not total amino acid load [19,20], although the acid content of these diets was not controlled.…”
Section: Effect Of Dietary Protein Restriction On Proteinuriamentioning
confidence: 99%
“…In experimental animals however, arginine supplementation actually amliorates both proteinuria and hyperfiltration in diabetic rats, and has no effect on urinary albumin excretion in rats with passive Heymann nephritis [73]. Thus, like the protein-renin interaction outlined above, there are conflicting data regarding the relationship between arginine, its effect on renal hemodynamics, and how that is then translated into alterations in permselectivity.…”
Section: Dietary Protein and Renal Hemodyamicsmentioning
confidence: 99%
“…In experimental studies in rats, dietary protein augmentation with a mixture of certain amino acids causes a prompt increase in urinary albumin excretion [62], while other amino acids, specifically branch chain amino acids, arginine, proline, glutamine, glutamate, aspartate or asparagine, are devoid of any effect on proteinuria [73]. Studies by D'Amico et al [92] and Walser [93] suggest that dietary protein composition may also be of importance in humans with renal disease.…”
Section: Dietary Protein and Renal Injurymentioning
confidence: 99%
“…The fractional renal clearance of albumin increases as well, suggesting that the permselective properties of the glomerular barrier are altered as a consequence of increased dietary protein content [1][2][3] or modified amino acid composition [4,5]. Paller and Hostetter [6] demonstrated that increasing dietary protein increased expression of the renin-angiotensin system in the rat.…”
Section: Introductionmentioning
confidence: 99%